1983
DOI: 10.1159/000233321
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lymphoid Cell DNA Synthesis by Metal Allergens at Various Concentrations

Abstract: Metal allergen concentrations inhibiting lymphoid cell DNA synthesis were tested on short-time cultured nonadherent and nonseparated thymic and splenic cells. With all tested metal allergens, the DNA-synthesis-inhibiting effect was more marked for nonadherent compared to nonseparated splenic cells. In thymocytes, a stronger inhibition of nonadherent cells was seen after addition of mercuric chloride. A protective or modifying role of adherent cells towards inhibiting or toxic effects of metal allergens in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…To date, most studies have been performed on animal cells, and the results have been extrapolated to the human immune system. In this regard, a number of investigations have demonstrated that mercurials inhibit rodent lymphocyte proliferation and function in vitro (Dieter et al, 1983;Nakatsuru et al, 1985;Nordlind, 1983;Pelletier et al, 1987). Furthermore, Petruccioli et al (1990) reported that monkeys exposed to HgCl 2 manifested reduced levels of serum IgG and IgM.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies have been performed on animal cells, and the results have been extrapolated to the human immune system. In this regard, a number of investigations have demonstrated that mercurials inhibit rodent lymphocyte proliferation and function in vitro (Dieter et al, 1983;Nakatsuru et al, 1985;Nordlind, 1983;Pelletier et al, 1987). Furthermore, Petruccioli et al (1990) reported that monkeys exposed to HgCl 2 manifested reduced levels of serum IgG and IgM.…”
Section: Introductionmentioning
confidence: 99%